Component for ion sensor based on polymer and carbon nanotube composite fuctionalized with metal-macrocyclic complex molecule, the ion sensor and method for manufacturing the ion sensor
Patent Information
- Application Number
- KR1020250024885
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2026-09-02
Smart Images

Figure PAT00007_ABST
Abstract
Description
Technology Field
[0001] Embodiments of the present invention relate to a component for an ion sensor based on a polymer and carbon nanotube composite material functionalized with a metal-macrocyclic composite molecule, an ion sensor, and a method for fabricating the same. Background Technology
[0002] Ion sensors can be utilized in various ways, such as for healthcare, hazardous environment detection, and water pollution control. For example, ion sensors can detect harmful heavy metal ions contained in solutions for the purpose of monitoring water pollution. However, conventional ion sensors have problems such as low selectivity and low sensitivity, material limitations, and difficulty in securing reliable sensor characteristics due to measurement technology.
[0003] [Prior Art No.]
[0004] Korean Patent Publication No. 10-2024-0108647 The problem to be solved
[0005] The present invention provides a component for an ion sensor based on a polymer and carbon nanotube composite material functionalized with a metal-macrocyclic composite molecule, an ion sensor, and a method for fabricating the same. means of solving the problem
[0006] The present invention provides an ion sensor sensing material characterized by comprising a polymer-carbon nanotube composite material in which a metal-macrocyclic composite molecule is chemically or physically functionalized, wherein the polymer-carbon nanotube composite material comprises carbon nanotubes and a polymer non-covalently bonded to the surface of the carbon nanotubes, and wherein the metal-macrocyclic composite molecule is formed by chelating a metal ion to the porphyrin center of the macrocyclic composite molecule in which the meso position of the porphyrin molecule is substituted with a positively charged functional group or a functional group that provides hydrogen bonding.
[0007] According to one aspect, the polymer may be characterized by including a pyridyl group.
[0008] According to another aspect, the positively charged functional group may be characterized as being a pyridinium group.
[0009] According to another aspect, the positively charged functional group may be characterized by including a counter anion.
[0010] According to another aspect, the functional group providing the hydrogen bond may be characterized by including at least one of urea, thiourea, squaramide, and croconamide, which are double hydrogen bond donors.
[0011] According to another aspect, the functional group providing the hydrogen bond may be characterized by including an electron-pulling group.
[0012] According to another aspect, the positively charged functional group and the functional group providing the hydrogen bond may be characterized as being directly connected or connected by an alkyl chain composed of carbon.
[0013] According to another aspect, the metal included in the metal-macrocyclic complex molecule may be characterized by including at least one of Be, Mg, Ca, Sr, Ba, Ra, Fe, Cd, Cr, Co, Cu, Pb, Mn, Hg, Ni, Pt, Sn, and Zn.
[0014] According to another aspect, the molecular weight (M) of the metal-macrocyclic complex molecule w ) may be characterized by being included in the range of 100 to 100,000 g / mol.
[0015] According to another aspect, the metal-macrocyclic complex molecule may be characterized by being represented by the following chemical formula 1, and
[0016] [Chemical Formula 1]
[0017]
[0018] In the above chemical formula 1, R1 is a positively charged functional group, X is a negatively charged counter-anion, and C n (n = 0~10) is an alkyl chain composed of carbon, R2 is an organic molecule containing a double hydrogen bond donor or electron-pulling group, and M is a metal atom.
[0019] According to another aspect, the metal-macrocyclic complex molecule may be characterized by being represented by the following chemical formula 1a, and
[0020] [Chemical Formula 1a]
[0021]
[0022] In the above chemical formula 1a, M is a metal atom.
[0023] The present invention provides an ion sensor comprising: a sensor substrate in which the ion sensor sensing material is bonded by a covalent bond; and a sensor electrode patterned on the top of the sensor substrate to detect an electrical signal of the ion sensing material.
[0024] According to one aspect, the sensor substrate may be characterized by comprising at least one of glass, silicon, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonates (PC), polyethersulfone (PES), polyimide (PI), cyclic olefin copolymer (COC), and poly-dimethylsiloxane (PDMS).
[0025] (a) a step of preparing a uniform polymer-carbon nanotube dispersion solution by mixing a polymer containing a pyridyl group with carbon nanotubes; (b) a step of preparing a sensing layer based on a polymer-carbon nanotube composite material by uniformly applying and bonding the polymer-carbon nanotube dispersion solution onto a sensor substrate having a patterned electrode and surface treated; (c) a step of preparing a metal-macrocyclic composite molecule; and (d) a step of fabricating an ion sensor by functionalizing the metal-macrocyclic composite molecule into the polymer-carbon nanotube composite material.
[0026] According to one aspect, in step (a) above, the polymer and the carbon nanotube are dispersed and mixed in a solvent, and the solvent may be characterized by comprising at least one solvent selected from ethanol, methanol, propanol, butanol, isopropyl alcohol (IPA), dimethylformamide (DMF), acetone, acetonitrile, toluene, tetrahydrofuran, 1,2-dichlorobenzene, water, and mixtures thereof.
[0027] According to another aspect, in step (b) above, the polymer-carbon nanotube dispersion solution may be applied to the sensor substrate using at least one coating process among a drop-coating process, a screen printing process, a spray coating process, a dip coating process, and an inkjet printing process.
[0028] According to another aspect, in step (b) above, the polymer may be characterized by forming a covalent bond through chemical bonding with a bromoalkyl chain functional group included in the sensor substrate that has been chemically modified through the surface treatment.
[0029] According to another aspect, in step (b) above, the polymer-carbon nanotube composite material may be characterized by being bonded to the surface of the sensor substrate at a temperature included in the range of 25°C to 300°C.
[0030] According to another aspect, in step (c) above, the metal-macrocyclic complex molecule may be formed by chelating a metal ion at the porphyrin center of the macrocyclic complex molecule, wherein the meso position of the porphyrin molecule is substituted with a positively charged functional group or a functional group that provides hydrogen bonding, and the synthesis temperature for chelating the metal ion may be included in the range of 25°C to 200°C.
[0031] According to another aspect, in step (d) above, a variety of metal-macrocyclic composite molecules are functionalized in the polymer-carbon nanotube composite material, and the electrical properties of the carbon nanotube change through one or more chemical interactions among electrostatic attraction, hydrogen bonding, and coordination bonding between the polymer-carbon nanotube composite material functionalized with the variety of metal-macrocyclic composite molecules and an ionic component contained in the solution, and the ion sensor detects the ionic component by measuring the change in electrical properties. Effects of the invention
[0032] It is possible to provide a component for an ion sensor based on a polymer and carbon nanotube composite material functionalized with a metal-macrocyclic composite molecule, an ion sensor, and a method for fabricating the same.
[0033] By fabricating a metal-macrocyclic composite molecule capable of forming multiple chemical reactions with ionic components contained in a solution and functionalizing the fabricated metal-macrocyclic composite molecule onto the surface of a polymer-carbon nanotube composite material, an ion sensor sensing material can be fabricated, and using this ion sensor sensing material, an ion sensor having high selectivity, enhanced sensitivity, and a low detection limit for specific ions can be fabricated.
[0034] Polymer-carbon nanotube composites functionalized with metal-macrocyclic complexes can form multiple chemical reactions with ions in solution, and by utilizing the characteristic of their electrical resistance changing in real time, they can be used as ion sensor detection materials. Since the metal-macrocyclic complexes contain functional groups capable of simultaneously forming hydrogen bonds, electrostatic attraction, or coordinate bonds, they exhibit superior ion detection characteristics and a lower detection limit compared to pure polymer-carbon nanotube detection materials that are not functionalized with metal-macrocyclic complexes. Brief explanation of the drawing
[0035] FIG. 1 is a diagram illustrating an example of a real-time field diagnostic ion sensor using a polymer-carbon nanotube-based sensing material functionalized with a metal-macrocyclic composite molecule in one embodiment of the present invention. FIG. 2 is a flowchart illustrating an example of a method for fabricating an ion sensor using a polymer-carbon nanotube-based sensing material functionalized with a metal-macrocyclic composite molecule in one embodiment of the present invention. FIG. 3 is a diagram illustrating an example of a poly(4-vinylpyridine)-carbon nanotube dispersion prepared according to Example 1 of the present invention. Figure 4 is a UV-Vis-NIR absorption graph of a poly(4-vinylpyridine)-carbon nanotube dispersion prepared according to Example 1 of the present invention. Figure 5 is a photograph of a poly(4-vinylpyridine)-carbon nanotube composite material bonded to a glass substrate fabricated according to Example 1 of the present invention. Figure 6 is a Raman spectroscopic analysis graph of a poly(4-vinylpyridine)-carbon nanotube composite material bonded to a glass substrate fabricated according to Example 1 of the present invention. FIG. 7 is a diagram illustrating an example of the chemical formula of a metal-macrocyclic complex molecule prepared according to Example 2 of the present invention. FIG. 8 is a diagram illustrating an example of the chemical formula of a metal-porphyrin-based metal-macrocyclic complex molecule combined with squaramide prepared according to Example 2 of the present invention. Figure 9 is a Fourier Transform Infrared Spectroscopy (FT-IR) analysis graph of CuP4SQ-P4VP-SWCNT fabricated according to Example 2 of the present invention. Figure 10 is an X-ray photoelectron spectroscopy (XPS) graph of CuP4SQ-P4VP-SWCNT fabricated according to Example 2 of the present invention. Figure 11 is a Fourier transform infrared spectroscopic analysis graph of ZnP4SQ-P4VP-SWCNT fabricated according to Example 2 of the present invention. Figure 12 is an X-ray photoelectron spectroscopy graph of ZnP4SQ-P4VP-SWCNT fabricated according to Example 2 of the present invention. FIG. 13 is a drawing illustrating an example of an ion sensor manufactured according to an embodiment of the present invention. Figure 14 is a graph comparing and evaluating the sensitivity of ion sensors fabricated based on the CuP4SQ-P4VP-SWCNT sensing material according to Example 2, Experimental Example 1, and Experimental Example 2 of the present invention to acetate anions, chloride ions, bromide ions, and nitrate ions. Figure 15 is a graph comparing and evaluating the sensitivity characteristics of ion sensors fabricated based on the CuP4SQ-P4VP-SWCNT sensing material according to Example 2, Experimental Example 1, and Experimental Example 2 of the present invention according to the concentration of acetate ions. FIG. 16 is a graph comparing and evaluating the sensitivity of ion sensors fabricated based on the ZnP4SQ-P4VP-SWCNT sensing material according to Example 2, Experimental Example 1, and Experimental Example 2 of the present invention to acetate anions, chloride ions, bromide ions, and nitrate ions. Figure 17 is a graph comparing and evaluating the sensitivity characteristics according to the concentration of acetate ions of ion sensors fabricated based on the ZnP4SQ-P4VP-SWCNT sensing material in Example 2, Experimental Example 1, and Experimental Example 2 of the present invention. FIG. 18 is a graph comparing and evaluating the sensitivity characteristics according to the concentration of acetate ions of ion sensors fabricated using unfunctionalized P4VP-SWCNT sensing materials according to Comparative Example 1, Experimental Example 1, and Experimental Example 2 of the present invention. FIG. 19 is a graph comparing and evaluating the detection characteristics of acetate anions of ion sensors fabricated according to Example 2, Comparative Example 1, Experimental Example 1, and Experimental Example 2 of the present invention. Specific details for implementing the invention
[0036] Hereinafter, embodiments will be described in detail with reference to the attached drawings.
[0037] Embodiments of the present invention relate to a sensing material for an ion sensor based on a polymer and carbon nanotube composite material functionalized with a metal-macro-ring composite molecule capable of detecting anions contained in a solution with high sensitivity and a low detection limit, an ion sensor using such a sensing material, and a method for fabricating the ion sensor.
[0038] Metal-macrocyclic complex molecules may include a macrocyclic molecular structure formed by substituting the meso position of a porphyrin molecule with an organic molecule containing a positively charged group or a group that provides hydrogen bonding, and may additionally be formed by chelating a metal ion at the center of the porphyrin molecule. Since metal-macrocyclic complex molecules can simultaneously chemically interact with an anionic component through electrostatic attraction, hydrogen bonding, or coordination bonding, they can exhibit excellent anion sensing characteristics and a low sensing limit.
[0039] In particular, selectivity toward anionic components can be exhibited due to differences in the intensity of the reaction to specific anionic components that occur depending on the type of chelated metal component and the group providing hydrogen bonds. Utilizing this characteristic, metal-macrocyclic composite molecules can be functionalized on the surface of electrically conductive carbon nanotube materials to be used as resistance-changing anion sensors. To achieve functionalization, the metal-macrocyclic composite molecules can form coordination bonds with polymers containing pyridyl groups or π-π stacking interactions with carbon nanotubes. Therefore, the metal-macrocyclic composite molecules can be functionalized on the surface of carbon nanotubes through non-covalent bonding.
[0040] Ion sensors can be fabricated by utilizing the principle that the electrical properties of carbon nanotubes change through chemical interaction between metal-macrocyclic complex molecules and specific anionic components, and since the degree of resistance change changes in real time depending on the concentration of specific ionic components, polymer-carbon nanotube composite materials functionalized with metal-macrocyclic complex molecules can be used as sensing materials for ion sensors capable of real-time ion detection.
[0041] FIG. 1 is a diagram illustrating an example of a real-time field diagnostic ion sensor using a polymer-carbon nanotube-based sensing material functionalized with a metal-macrocyclic composite molecule in one embodiment of the present invention. In this embodiment, an example of an ion sensor comprising a sensor substrate (101), an electrode (102), a surface bonding (103), a polymer (104), a carbon nanotube (105), and a metal-macrocyclic composite molecule (106) is shown.
[0042] The ion sensor can detect ionic components (107) contained in a solution with high sensitivity and a low detection limit. To this end, a metal-macrocyclic composite molecule (106) capable of interacting with specific ionic components (107) through multiple chemical reactions can be functionalized through covalent bonding to a polymer (104) or non-covalent bonding to the surface of a carbon nanotube (105). The metal-macrocyclic composite molecule (106) may include functional groups capable of simultaneously forming electrostatic attraction, hydrogen bonding, or coordination bonding with specific ionic components (107), and may chemically interact multiple times with the ionic components (107). Through these multiple chemical interactions of the metal-macrocyclic composite molecule (106), the ion sensor can exhibit high sensitivity and a low detection limit for specific anions. In addition, the metal-macrocyclic complex molecule (106) may exhibit different sensitivities to specific anionic components due to different chemical reaction characteristics depending on the type of metal at the center of the porphyrin.
[0043] The sensing material of the ion sensor may be composed of a polymer (104)-carbon nanotube (105) composite material formed by combining a carbon nanotube (105) exhibiting electrical conductivity and a polymer (104). This polymer (104)-carbon nanotube (105) composite material may be coated on a sensor substrate (101) capable of measuring electrical conductivity or on the top of an electrode (102) patterned on the top of the sensor substrate (101) and utilized as a sensing material for a resistance-changing ion sensor. The polymer (104) physically bonded to the surface of the carbon nanotube (105) may be bonded to the sensor substrate (101) through covalent bonding, thereby possessing strong mechanical durability. For example, a polymer (104) containing a pyridyl group can form a covalent bond through chemical bonding (surface bonding (103)) with a bromoalkyl functional group included on the top of a chemically modified sensor substrate (101).
[0044] The metal-macrocyclic complex molecule (106) may include a porphyrin structure. The porphyrin may form a metal-porphyrin compound in which a metal atom is substituted through chelation with various cations (metal ions). Additionally, the porphyrin may include a meso-substituted functional group. For example, the meso position of the porphyrin may be substituted with a pyridyl group, thereby including a porphyrin structure having four pyridyl groups. Furthermore, the meso-substituted porphyrin may include additional functional groups capable of forming various chemical interactions. Here, the various chemical interactions may simultaneously include electrostatic attraction through the cationic functional group, hydrogen bonding through the hydrogen bonding functional group, or coordinate bonding through the metal atom. The hydrogen bonding functional group may include a dual-hydrogen bond donor functional group. For example, the double hydrogen bond donor may include at least one of urea, thiourea, squaramide, or croconamide. The functional group substituted at the meso position of the porphyrin and the double hydrogen bond donor functional group may be directly bonded to each other or connected through a carbon-based alkyl chain. The number of carbons in the alkyl chain may be in the range between 0 (direct bonding) and 10. To maximize hydrogen bonding, the double hydrogen bond donor may further include an electron-withdrawing group in the macrocyclic complex. Additionally, the cationic functional group forming the ionic bond may include pyridinium, and the cationic functional group may include a counter anion.
[0045] In one embodiment, the metal-macrocyclic complex molecule (106) can be represented as shown in Chemical Formula 1 below.
[0046] [Chemical Formula 1]
[0047]
[0048] In this chemical formula 1, R1 is a positively charged functional group or a group containing such a functional group, X is a negatively charged counter-anion, and C n (n = 0~10) is an alkyl chain composed of carbon, R2 is a group of organic molecules including a double hydrogen bond donor or an electron-pulling group, and M may be a metal atom.
[0049] In a more specific embodiment, the metal-macrocyclic complex molecule (106) can be represented as shown in the following chemical formula 1a.
[0050] [Chemical Formula 1a]
[0051]
[0052] In the above chemical formula 1a, M may include any one of the metal atoms Be, Mg, Ca, Sr, Ba, Ra, Fe, Cd, Cr, Co, Cu, Pb, Mn, Hg, Ni, Pt, Sn, and Zn.
[0053] The metal-macrocyclic composite molecule (106) can be functionalized in the polymer (104)-carbon nanotube (105) composite material through chemical bonding. For example, a coordinate bond can be formed through chemical interaction between the metal of the metal-macrocyclic composite molecule (106) and the polymer (104) containing a non-covalent electron pair. As a more specific example, the polymer (104) containing a pyridyl group can be chemically functionalized through a coordinate bond with the metal-macrocyclic composite molecule (106) via the non-covalent electron pair possessed by the nitrogen atom of the pyridyl group.
[0054] The metal-macrocyclic composite molecule (106) can be physically functionalized in the polymer (104)-carbon nanotube (105) composite material through π-π stacking interactions with the polymer (104) or carbon nanotube (105). In other words, the metal-macrocyclic composite molecule (106) can be functionalized in the polymer (104)-carbon nanotube (105) composite material by inducing intermolecular bonding through the π-π stacking interactions of the aromatic rings contained in the metal-macrocyclic composite molecule (106), the polymer (104), or the carbon nanotube (105).
[0055] In this way, the metal-macrocyclic composite molecule (106) can be functionalized by chemically functionalizing the polymer (104) or by bonding it to the surface of the carbon nanotube (105) through a non-covalent bonding method, and the polymer (104)-carbon nanotube (105) composite material functionalized with the metal-macrocyclic composite molecule (106) can form a sensing material for an ion sensor through physical adsorption.
[0056] When a specific ionic component (107) is injected into a polymer (104)-carbon nanotube (105) composite material functionalized with a metal-macrocyclic composite molecule (106), the electrical properties of the carbon nanotube (105) can be changed through multiple chemical reactions. Therefore, the polymer (104)-carbon nanotube (105) composite material functionalized with a metal-macrocyclic composite molecule (106) can exhibit improved sensitivity or a lower detection limit compared to a polymer (104)-carbon nanotube (105) composite material not functionalized with a metal-macrocyclic composite molecule (106), and can exhibit selective detection characteristics for the ionic component (107). Changes in electrical properties of the polymer (104)-carbon nanotube (105) composite material functionalized with a metal-macrocyclic composite molecule (106) can be measured as resistance change signals through an electrode (102) patterned on the top of the sensor substrate (101).
[0057] As such, the ion sensor sensing material according to the present embodiment may include a polymer (104)-carbon nanotube (105) composite material in which a metal-macrocyclic composite molecule (106) is chemically or physically functionalized. At this time, the polymer (104)-carbon nanotube (105) composite material may include a carbon nanotube (105) and a polymer (104) non-covalently bonded to the surface of the carbon nanotube (105), and the metal-macrocyclic composite molecule (106) may be formed by chelating a metal ion to the porphyrin center of a macrocyclic composite molecule in which the meso position of the porphyrin molecule is substituted with a positively charged functional group or a functional group that provides hydrogen bonding.
[0058] Additionally, an ion sensor may be provided comprising a sensor substrate (101) to which such an ion sensor sensing material is bonded by a covalent bond, and a sensor electrode (electrode (102)) patterned on the top of the sensor substrate (101) to detect an electrical signal of the ion sensing material. The ion sensor can detect a specific ion component (107) with enhanced sensitivity and a low detection limit through multiple chemical reactions between the ion component (107) contained in the solution and the ion sensor sensing material.
[0059] The polymer (104) may comprise carbon chains functionalized with pyridyl groups containing non-covalent electron pairs. The molecular weight (M) of such polymer w ) may be included in the range of 10,000 to 5,000,000 g / mol.
[0060] Additionally, the carbon nanotube (105) may include single-walled to multi-walled carbon nanotubes, and may include at least one of carbon nanotubes exhibiting metallic properties and carbon nanotubes exhibiting semiconductor properties.
[0061] A polymer (104)-carbon nanotube (105) composite material can be formed as the polymer (104) is physically bonded to the surface of the carbon nanotube (105) through non-covalent bonding.
[0062] A polymer (104)-carbon nanotube (105) composite material may be coated on the top of a sensor substrate (101) patterned with an electrode (102) capable of evaluating electrical properties. The top of the sensor substrate (101) may include functional groups capable of forming chemical covalent bonds with the polymer (104) of the polymer (104)-carbon nanotube (105) composite material through surface treatment. Here, the functional groups included on the top of the sensor substrate (101) may include bromoalkyl chains. In this case, the polymer (104)-carbon nanotube (105) composite material may include a coating layer that is mechanically strongly bonded to the top of the sensor substrate (101) through covalent bonding. The thickness of this coating layer may be in the range of 1 nm to 500 μm.
[0063] Additionally, the sensor substrate (101) may include at least one of glass, silicon, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonates (PC), polyethersulfone (PES), polyimide (PI), cyclic olefin copolymer (COC), and poly-dimethylsiloxane (PDMS).
[0064] Meanwhile, the porphyrin molecule included in the metal-macrocyclic complex molecule (106) may include a macrocyclic structure in which four pyrrole rings are connected. This porphyrin molecule may include four pyridyl groups as functional groups through mesopositional substitution. The mesopositionally substituted porphyrin molecule may further include a positively charged functional group or a functional group capable of providing hydrogen bonds at the mesopositional functional group. Here, the positively charged functional group may include pyridinium. Additionally, the functional group providing hydrogen bonds may include a double hydrogen bond donor. The double hydrogen bond donor may include at least one of urea, thiourea, squaramide, or croconamide. Additionally, to maximize the hydrogen bonding of the double hydrogen bond donor, an electron-pulling group may be further included. The electron-pulling group may include at least one CF3 functional group bonded to the meta to para position of the phenyl group.
[0065] Additionally, mesopositionally substituted porphyrins can form metal-macrocyclic complex molecules (106) that are chemically bonded to metals (Be, Mg, Ca, Sr, Ba, Ra, Fe, Cd, Cr, Co, Cu, Pb, Mn, Hg, Ni, Pt, Sn, and / or Zn) through chelation reactions with various metal ions. The molecular weight (M) of such metal-macrocyclic complex molecules (106) w ) may be included in the range of 100 to 100,000 g / mol. The metal-macrocyclic complex molecule (106) may have multiple chemical interactions with specific ionic components (107) in the solution.
[0066] In one embodiment, a metal-macrocyclic composite molecule (106) can be functionalized in a polymer (104)-carbon nanotube (105) composite material through chemical coordination bonding with a polymer (104) containing a pyridyl group.
[0067] In another embodiment, a metal-macrocyclic composite molecule (106) can be physically bonded to the surface of a carbon nanotube (105) through pi-pi interactions and functionalized in a polymer (104)-carbon nanotube (105) composite material.
[0068] In another embodiment, a metal-macrocyclic composite molecule (106) or a polymer (104) can be composited into a polymer (104)-carbon nanotube (105) composite material through non-covalent bonding on the surface of a carbon nanotube (105).
[0069] As previously explained, a polymer (104)-carbon nanotube (105) composite material functionalized with a metal-macrocyclic composite molecule (106) can be utilized as a sensing material for an ion sensor capable of multiple chemical interactions with a specific ionic component (107). This ion sensor sensing material can be included in a resistance-changing ion sensor in which electrical resistance changes when a specific ionic component (107) is injected. The resistance change of the ion sensor sensing material can be in the range of 100 Ω to 100 MΩ. The ionic component (107) is a nitrate ion (NO3 - ), chloride ion (Cl - ), acetate ion (CH3COO - ), dihydrogen phosphate ion (H2PO4) - ), hydrogen sulfate ion (HSO4) - ) to bromide ions (Br - It may include at least one of ). Such ion sensor detection materials can be utilized in ion sensors capable of real-time monitoring of hazardous environments and water quality.
[0070] FIG. 2 is a flowchart illustrating an example of a method for fabricating an ion sensor using a polymer-carbon nanotube-based sensing material functionalized with a metal-macrocyclic composite molecule in one embodiment of the present invention. The method for fabricating an ion sensor according to the present embodiment may include the steps of: mixing a polymer containing a pyridyl group with a carbon nanotube to prepare a uniform polymer-carbon nanotube dispersion solution (210); uniformly applying and bonding the polymer-carbon nanotube dispersion solution to a sensor substrate on which an electrode is patterned and surface treated to produce a sensing layer based on a polymer-carbon nanotube composite material (220); preparing a metal-macrocyclic composite molecule (230); and fabricating an ion sensor by functionalizing the metal-macrocyclic composite molecule in the polymer-carbon nanotube composite material (240).
[0071] In step (210), the polymer and carbon nanotubes can be mixed by dispersing them in a solvent. At this time, the solvent may include at least one solvent selected from ethanol, methanol, propanol, butanol, isopropyl alcohol (IPA), dimethylformamide (DMF), acetone, acetonitrile, toluene, tetrahydrofuran, 1,2-dichlorobenzene, water, and mixtures thereof.
[0072] Additionally, in step (210), the polymer included in the dispersion solution may be included in the dispersion solution in a weight in the range of 0.01 to 500 relative to the weight of the carbon nanotubes.
[0073] Additionally, in step (210), the polymer can be physically bonded to the surface of the carbon nanotube through non-covalent bonding using poly(4-vinylpyridine).
[0074] Additionally, in step (210), the carbon nanotube may include a carbon nanotube having multiple walls or a single wall.
[0075] Additionally, in step (210), the carbon nanotubes may have metallic and semiconductor properties.
[0076] In step (220), the electrode patterned on the sensor substrate can be formed on the sensor substrate through any one of a conductive paste coating, a physical vapor deposition method, and a chemical vapor deposition method.
[0077] Additionally, in step (220), the sensor substrate may include at least one of glass, silicon, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonates (PC), polyethersulfone (PES), polyimide (PI), cyclic olefin copolymer (COC), and poly-dimethylsiloxane (PDMS).
[0078] Additionally, in step (220), bromoalkyl chain functional groups can be formed on the top of the sensor substrate by covalent bonding through surface treatment of the sensor substrate.
[0079] Additionally, in step (220), the polymer can form a covalent bond through chemical bonding with a bromoalkyl chain functional group included in the sensor substrate that has been chemically modified through surface treatment.
[0080] Additionally, in step (220), the temperature at which the polymer-carbon nanotube composite material is bonded to the surface of the sensor substrate may be in the range of 25°C to 300°C.
[0081] Additionally, in step (220), the application of the polymer-carbon nanotube dispersion solution may be performed by at least one coating process among a drop-coating process, a screen printing process, a spray coating process, a dip coating process and an inkjet printing process.
[0082] Additionally, in step (220), depending on the coating process method, the coating thickness of the polymer-carbon nanotube composite material may be in the range of 1 nm to 500 μm.
[0083] In step (230), the metal-macrocyclic complex molecule can be formed using a porphyrin molecule formed by connecting four pyrrole rings.
[0084] Additionally, in step (230), the metal-macrocyclic complex molecule has Be at the porphyrin center 2+ , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , Ra 2+ , Fe 2+ , Cd 2+ , Cr 2+ , Co 2+ , Cu 2+ , Pb 2+ , Mn 2+ , Hg 2+ , Ni 2+ , Pt 2+ , Sn 2+ , Zn 2+ It can be manufactured by chelating one of the metal ions.
[0085] In addition, in step (230), a macrocyclic complex molecule can be produced by substituting the meso positions of the porphyrin molecule to form functional groups or cationic functional groups that provide hydrogen bonds.
[0086] Additionally, in step (230), the metal-macrocyclic complex molecule may be formed by chelating a metal ion at the center of the macrocyclic complex molecule, wherein the meso position of the porphyrin molecule is substituted with a positively charged functional group or a functional group that provides hydrogen bonding. At this time, the synthesis temperature for chelating the metal ion may be included in the range of 25°C to 200°C.
[0087] In step (240), the metal-macrocyclic composite molecule may have a weight in the range of 0.01 to 500 relative to the weight of the polymer.
[0088] Additionally, in step (240), the metal-macrocyclic composite molecule can be functionalized into the polymer-carbon nanotube composite material through chemical coordination bonding to the polymer containing non-covalent electron pairs.
[0089] Additionally, in step (240), the metal-macrocyclic composite molecule can be physically functionalized in the polymer-carbon nanotube composite material through pi-pi bonds containing aromatics of the polymer or carbon nanotube.
[0090] Additionally, in step (240), the solvent for functionalizing the metal-macrocyclic complex molecule may include at least one solvent selected from ethanol, methanol, propanol, butanol, isopropyl alcohol (IPA), dimethylformamide (DMF), acetone, acetonitrile, toluene, tetrahydrofuran, 1,2-dichlorobenzene, water, and mixtures thereof.
[0091] An ion sensor detection material comprising a polymer-carbon nanotube composite material functionalized with metal-macrocyclic complex molecules can transmit electrical resistance change signals in real time through patterned electrodes. At this time, the ion sensor can be fabricated by forming a solution chamber at the top of the ion sensor detection material to inject a solution for evaluating ion detection characteristics. The solution chamber can be fabricated as a cylindrical structure with a diameter ranging from 0.1 mm to 50 mm. An ion sensor detection material comprising a polymer-carbon nanotube composite material functionalized with various metal-macrocyclic complex molecules can be utilized as an ion sensor detection material that converts into electrical signals through chemical interactions with multiple ionic components contained in the solution. Through this, the ion sensor can detect ionic components in the solution in real time with high sensitivity and a low detection limit by detecting resistance changes according to the concentration of specific ions.
[0092] Example 1: Fabrication of a polymer-carbon nanotube composite material chemically bonded to a substrate
[0093] In Example 1, the fabrication of a polymer-carbon nanotube composite material chemically bonded to a substrate is described by applying a uniformly dispersed polymer-carbon nanotube solution to a chemically treated substrate. To prepare the uniformly dispersed polymer-carbon nanotube solution, 10 mg of poly(4-vinylpyridine) (P4VP), a polymer containing pyridiyl groups, was mixed with 10 mL of dimethylformamide ( N,NA mixed solution is prepared by completely dissolving the material in dimethylformamide (DMF) and then adding 1 mg of single-walled carbon nanotubes (SWCNTs). The mixed solution is homogenized by dispersing it for 1 hour using ultrasonic dispersion. Through the ultrasonic dispersion process, poly(4-vinylpyridine) is physically bound to the surface of the carbon nanotubes, thereby improving dispersibility. Undispersed carbon nanotubes can be removed using a centrifuge. Through centrifugation, the solution is separated into a supernatant and a precipitate; since the supernatant contains a poly(4-vinylpyridine)-carbon nanotube complex, the supernatant is obtained to produce a uniformly dispersed poly(4-vinylpyridine)-carbon nanotube dispersion.
[0094] In order to produce a substrate that has undergone the above chemical treatment, in Example 1, a glass substrate was washed in acetone for 15 minutes, and then immersed in a toluene solution containing (3-bromopropyl)trichlorosilane (BPTS) at a volume ratio of 1% and a chemical reaction was carried out for 12 hours. After the reaction was finished, the glass substrate was washed with toluene to produce a glass substrate containing a bromoalkyl functional group.
[0095] In order to fabricate a polymer-carbon nanotube composite material chemically bonded to the substrate, the uniformly dispersed poly(4-vinylpyridine)-carbon nanotube dispersion can be uniformly applied to the chemically treated substrate by at least one coating process among drop-coating, screen printing, spray coating, dip coating, and inkjet printing. In Example 1, the dispersion was applied to the chemically treated glass substrate via a spray coating process. The spray coating process is carried out with the glass substrate heated to 130°C to induce chemical bonding between the pyridyl groups of the poly(4-vinylpyridine)-carbon nanotubes and the bromoalkyl functional groups contained in the chemically treated glass substrate, thereby exhibiting strong mechanical durability. The composite material can be applied in various forms depending on the shape of the masking layer. The poly(4-vinylpyridine)-carbon nanotube composite material coated on a glass substrate was washed with dichloromethane to remove the chemically unbonded composite material. FIG. 3 is a diagram illustrating an example of a poly(4-vinylpyridine)-carbon nanotube dispersion prepared according to Example 1 of the present invention.
[0096] Figure 4 is a UV-Vis-NIR absorption graph of a poly(4-vinylpyridine)-carbon nanotube dispersion prepared according to Example 1 of the present invention. According to the graph in Figure 4, the absorbance is 0.298 at a wavelength of 1163 nm. The absorbances around the wavelengths of 800-1600 nm and 600-800 nm are peaks due to carbon nanotubes exhibiting semiconductor properties, and the peak appearing at the wavelength of 400-600 nm is a peak due to carbon nanotubes exhibiting metallic properties.
[0097] Figure 5 is a photograph of a poly(4-vinylpyridine)-carbon nanotube composite material bonded to a glass substrate fabricated according to Example 1 of the present invention.
[0098] Figure 6 shows Raman spectroscopic analysis graphs of a poly(4-vinylpyridine)-carbon nanotube composite material bonded to a glass substrate fabricated according to Example 1 of the present invention. The Raman spectroscopic graph of Figure 6 is G + Analysis was performed by normalizing with bands. After forming the poly(4-vinylpyridine)-carbon nanotube composite material, G - The band strength decreased and G + By observing the change in the position of the band, it was determined that poly(4-vinylpyridine) and carbon nanotubes were composited.
[0099] Example 2: Fabrication of Polymer-Carbon Nanotube Based Ion Sensing Material Functionalized with Metal-Macrocyclic Composite Molecules
[0100] In Example 2, the fabrication of an ion-sensing material is described by functionalizing a metal-macrocyclic composite molecule into the poly(4-vinylpyridine)-carbon nanotube composite material prepared in Example 1. The synthesis of the metal-macrocyclic composite molecule was carried out by bonding a double hydrogen bond donor to a metal-porphyrin in which a pyridyl group is meso-substituted.
[0101] The synthesis of the above-mentioned pyridyl group meso-substituted metal-porphyrin was achieved by chelating a metal ion to the pyridyl group meso-substituted porphyrin. Specifically, the porphyrin was dimethylformamide ( N,N A mixed solution was prepared by dissolving the metal precursor in dimethylformamide (DMF) and adding the metal precursor, and the mixed solution was heated to 160 °C for 12 hours and refluxed to carry out the chelation reaction. After removing the solvent from the reaction solution, the residue was purified to obtain metal-porphyrin.
[0102] The above double hydrogen bond donor can be represented by the following chemical formula 3.
[0103] [Chemical Formula 3]
[0104] R2-C n -*
[0105] In the above chemical formula 3, R2 is an organic molecule comprising a double hydrogen bond donor or an electron-pulling group, C n (n=1-10) is an alkyl chain composed of n carbons, and * is a leaving group that may be a bonding site formed with the pyridyl group of the metal-porphyrin. The organic molecule may include at least one of urea, thiourea, squaramide, or croconamide, and may include an electron withdrawing group having a structure in which CF3 groups are substituted at the meta to para positions of the phenyl group.
[0106] In Example 2, a double hydrogen bond donor molecule was utilized that consists of a squaramide, a C3 alkyl chain, and a leaving group containing a bromine (Br) atom, which forms a bond with the metal-porphyrin. Through a quaternization reaction between the bromine atom and the pyridyl group of the metal-porphyrin, the bromine atom is removed, and a bond is formed between the nitrogen atom of the pyridyl group and the alkyl chain of the squaramide molecule. During the quaternization reaction, the pyridyl group is converted into a pyridinium group, thereby synthesizing a metal-macrocyclic complex molecule (MP4SQ, M= Zn, Cu, Co, Ni) that simultaneously possesses a double hydrogen bond donor functional group and a positively charged functional group.
[0107] Specifically, the metal-porphyrin with the meso-substituted pyridyl group and the double hydrogen bond donor molecule were completely dissolved in dimethylformamide, and then the mixed solution was heated to 110 °C and a chemical reaction was carried out for 72 hours. The mixed solution, after the reaction was completed, was dispersed in ether to form a precipitate. The obtained precipitate was redispersed in acetonitrile, and through a purification process, a metal-macrocyclic complex molecule in which a double hydrogen bond donor is bonded to the metal-porphyrin was obtained.
[0108] To functionalize the above metal-macrocyclic composite molecule into the poly(4-vinylpyridine)-carbon nanotube composite material prepared according to Example 1, a coating solution was prepared by dissolving the metal-macrocyclic composite molecule in an organic solvent. In this Example 2, a coating solution was prepared by completely dissolving 1 mg of the metal-macrocyclic composite molecule in a mixed solution of 1.5 mL of methanol and 3 mL of acetonitrile. The coating was carried out by dip coating. Specifically, the coating was performed by immersing a glass substrate coated with the poly(4-vinylpyridine)-carbon nanotube composite material in the coating solution for 5 minutes. After coating, the composite material was dried at 60°C for 10 minutes, washed with acetonitrile, and then further dried sufficiently at 60°C to produce an ion-sensing material in which metal-macrocyclic composite molecules are functionalized through coordination bonding or pi-pi bonding to poly(4-vinylpyridine)-carbon nanotubes.
[0109] FIG. 7 illustrates an example of the chemical formula of a metal-macrocyclic complex molecule prepared according to Example 2 of the present invention. FIG. 7 shows the chemical formula of a metal-porphyrin-based metal-macrocyclic complex molecule to which a double hydrogen bond donor is bonded. Here, M is a metal atom, R1 is a positively charged functional group, and C n silver C1 to C connecting R1 and R2 10The alkyl chain of R2 is an organic molecule composed of a double hydrogen bond donor molecule or an electron-pulling functional group, and X is a counter anion formed through a quaternary reaction that is bonded to R1, which has a positive charge, by electrostatic attraction.
[0110] FIG. 8 illustrates an example of the chemical formula of a metal-porphyrin-based metal-macrocyclic complex molecule combined with squaramide prepared according to Example 2 of the present invention. FIG. 8 is an example of a specific chemical formula of a metal-macrocyclic complex molecule (MP4SQ, M= Zn, Cu, Co, Ni), wherein a metal atom is chelated at the center of the metal-macrocyclic complex molecule and contains one of zinc, copper, cobalt, or nickel. As a positively charged functional group, a para-pyridinium group is bonded to the meso region of the porphyrin, and an electron-withdrawing group having a structure in which a squaramide double hydrogen bond donor or two CF3 groups are substituted at the meta position of the phenyl group via a C3 alkyl chain to the nitrogen atom of the pyridinium is bonded. Finally, as a counter-anionic component, a bromide ion is bonded to the positively charged functional group through electrostatic attraction.
[0111] Figure 9 is a Fourier Transform Infrared Spectroscopy (FT-IR) analysis graph of CuP4SQ-P4VP-SWCNT fabricated according to Example 2 of the present invention. Figure 9 shows a Fourier Transform Infrared Spectroscopy graph to elucidate the functionalization of a metal-macrocyclic composite molecule (CuP4SQ) in which copper is chelated onto a poly(4-vinylpyridine)-carbon nanotube composite material. In the graph of the CuP4SQ-functionalized poly(4-vinylpyridine)-carbon nanotube (CuP4SQ-P4VP-SWCNT), the peak corresponding to the ring breathing mode of squaramide is at 1793 cm⁻¹. -1Functionation was identified by confirming what appears in.
[0112] Figure 10 is an X-ray photoelectron spectroscopy (XPS) graph of CuP4SQ-P4VP-SWCNT fabricated according to Example 2 of the present invention. Figure 10 shows an X-ray photoelectron spectroscopy graph of the copper element to elucidate the functionalization of CuP4SQ in the poly(4-vinylpyridine)-carbon nanotube composite material. The functionalization was elucidated by confirming the peak for the copper element in CuP4SQ-P4VP-SWCNT.
[0113] Figure 11 is a Fourier transform infrared spectral analysis graph of ZnP4SQ-P4VP-SWCNT fabricated according to Example 2 of the present invention. Figure 11 shows a Fourier transform infrared spectral graph to elucidate the functionalization of a metal-macrocyclic composite molecule (ZnP4SQ) chelated with zinc in a poly(4-vinylpyridine)-carbon nanotube composite material. In the graph of the poly(4-vinylpyridine)-carbon nanotube (ZnP4SQ-P4VP-SWCNT) functionalized with ZnP4SQ, the peak corresponding to the ring breathing mode of squaramide is at 1793 cm⁻¹. -1 Functionation was identified by confirming what appears in.
[0114] Figure 12 is an X-ray photoelectron spectroscopy graph of ZnP4SQ-P4VP-SWCNT fabricated according to Example 2 of the present invention. Figure 12 shows an X-ray photoelectron spectroscopy graph of the zinc element to investigate the functionalization of ZnP4SQ in the poly(4-vinylpyridine)-carbon nanotube composite material. The functionalization was investigated by confirming the peak for the zinc element in ZnP4SQ-P4VP-SWCNT.
[0115] Comparative Example 1: Fabrication of a polymer-carbon nanotube-based ion-sensing material not functionalized with metal-macrocyclic complex molecules
[0116] In Comparative Example 1, in order to observe the effect of metal-macrocyclic composite molecules on ion sensing, a poly(4-vinylpyridine)-carbon nanotube (P4VP-SWCNT) composite material was prepared as described in Example 1 above, and an ion sensing material was prepared by omitting the functionalization process of Example 2 above.
[0117] Experimental Example 1: Fabrication of an ion sensor using the sensing material prepared according to Example 1, Example 2, and Comparative Example 1
[0118] An ion sensor was fabricated to detect ions contained in a solution using an ion-sensing material prepared according to Example 1, Example 2, and Comparative Example 1. To fabricate the ion sensor in Experimental Example 1, a polydimethylsiloxane (PDMS) with a cylindrical perforation located in the center was attached to the top of the composite material to form a cylindrical solution chamber capable of injecting a solution into the top of the composite material. The invention is characterized by the ability to induce a chemical interaction between the composite material and the ionic components within the solution by injecting a solution containing ions into the solution chamber. Additionally, electrodes were formed by coating both ends of the composite material with a conductive paste. The electrical resistance of the composite material can be measured through the electrodes. Therefore, the ion sensor is characterized by inducing a chemical reaction with the composite material when a solution is injected into the solution chamber, and measuring the change in the electrical resistance of the composite material caused by the chemical reaction in real time through the electrodes.
[0119] FIG. 13 is a diagram illustrating an example of an ion sensor fabricated according to an embodiment of the present invention. A cylindrical solution chamber is formed on the top of an ion monitoring material using PDMS. By injecting a solution into the solution chamber to induce a chemical reaction with the ion sensing material, a change in resistance can be observed in real time through electrodes at both ends of the ion sensing material.
[0120] Experimental Example 2: Evaluation of ion sensing characteristics of the ion sensor fabricated according to Experimental Example 1
[0121] In Experimental Example 2, a method for evaluating ion detection characteristics using the ion sensor fabricated according to Experimental Example 1 and detection characteristics for anions are described. To evaluate ion detection characteristics, sensitivity is measured by stabilizing the ion sensor by injecting a pure solution that does not contain ions, and then observing the change in resistance that occurs when a solution containing ions is injected. The sensitivity of the sensor can be calculated as (R-R0) / R0×100%. Here, R0 is the resistance of the sensor stabilized after injecting a pure solution that does not contain ions, and R is the resistance that appears when a solution containing ions is injected.
[0122] Specifically, in Experimental Example 2, to detect anions contained in acetonitrile, 10 μL of acetonitrile was injected into the ion sensor and a stabilization process was carried out for 2-3 minutes. Then, 2 μL of an acetonitrile solution containing anions was injected, and the change in resistance was observed to evaluate the sensitivity of the sensor. The sensitivity of the sensor is (R-R0) / R0×100%, where R0 is the resistance of the sensor stabilized after injecting acetonitrile without anions, and R is the resistance that appears when an acetonitrile solution containing anions is injected. At this time, a source meter of the Keithley 2400 model was used to measure the change in resistance.
[0123] FIG. 14 shows an acetate anion (CH3COO) at a concentration of 167 μM in an ion sensor made of a CuP4SQ-P4VP-SWCNT ion sensing material fabricated according to Example 2 and Experimental Example 1. - ), chloride ion (Cl - ), bromide ion (Br - ) and nitrate ions (NO3 -The graph shows the real-time resistance change and average sensitivity for ). The CuP4SQ-P4VP-SWCNT-based ion sensor showed high sensitivity of 31.93 ± 1.76% for acetate anions, while showing low sensitivity of 5.52% or less for chloride, bromide, and nitrate ions, confirming excellent selectivity for acetate anions.
[0124] Figure 15 is a graph showing the change in sensitivity according to acetate anion concentration of the CuP4SQ-P4VP-SWCNT-based ion sensor fabricated according to Example 2 and Experimental Example 1. Measurements were taken at acetate anion concentrations ranging from 1.67 to 167 μM.
[0125] FIG. 16 shows an ion sensor made of a ZnP4SQ-P4VP-SWCNT ion sensing material fabricated according to Example 2 and Experimental Example 1, at a concentration of 167 μM acetate anion (CH3COO - ), chloride ion (Cl - ), bromide ion (Br - ) and nitrate ions (NO3 - The graph shows the real-time resistance change and average sensitivity for ). The ZnP4SQ-P4VP-SWCNT-based ion sensor showed high sensitivity of 43.45 ± 2.29% for acetate anions, while showing low sensitivity of 4.34% or less for chloride, bromide, and nitrate ions, confirming excellent selectivity for acetate anions.
[0126] Figure 17 is a graph showing the change in sensitivity according to acetate anion concentration of the ZnP4SQ-P4VP-SWCNT-based ion sensor fabricated according to Example 2 and Experimental Example 1. Measurements were taken at acetate anion concentrations ranging from 1.67 to 167 μM.
[0127] Figure 18 is a graph showing the change in sensitivity according to acetate anion concentration of an unfunctionalized P4VP-SWCNT-based ion sensor fabricated according to Comparative Example 1. Measurements were taken in the range of acetate anion concentrations from 1.67 to 167 μM, and a sensitivity of 10.52% was observed for 167 μM acetate anion.
[0128] Figure 19 is a graph comparing the sensitivity of ion sensors fabricated according to Example 2, Experimental Example 1, and Comparative Example 1 to 167 μM acetate anions. Compared to the unfunctionalized P4VP-SWCNT, ZnP4SQ-P4VP-SWCNT showed a sensitivity that increased by 3.99 times, and CuP4SQ-P4VP-SWCNT showed a sensitivity that increased by 3.3 times.
[0129] The foregoing description is merely an illustrative explanation of the technical concept of the present invention, and those skilled in the art to which the present invention pertains will be able to make various modifications and variations within the scope of the essential characteristics of the present invention. Accordingly, the embodiments described in the present invention are intended to explain, not limit, the technical concept of the present invention, and are not limited to such embodiments. The scope of protection of the present invention shall be interpreted by the claims below, and all technical concepts within an equivalent scope shall be interpreted as being included within the scope of rights of the present invention. Explanation of the symbols
[0130] 101: Sensor board 102: Electrode 103: Surface bonding 104: Polymer 105: Carbon nanotubes 106: Metal-macrocyclic complex molecule 107: Ionic components
Claims
Claim 1 An ion sensor sensing material comprising a polymer-carbon nanotube composite material in which a metal-macrocyclic composite molecule is chemically or physically functionalized, wherein the polymer-carbon nanotube composite material comprises carbon nanotubes and a polymer non-covalently bonded to the surface of the carbon nanotubes, and wherein the metal-macrocyclic composite molecule is formed by chelating a metal ion to the porphyrin center of a macrocyclic composite molecule in which the meso position of the porphyrin molecule is substituted with a positively charged functional group or a functional group that provides hydrogen bonding. Claim 2 An ion sensor sensing material according to claim 1, characterized in that the polymer comprises a pyridyl group. Claim 3 An ion sensor sensing material according to claim 1, characterized in that the positively charged functional group is a pyridinium group. Claim 4 An ion sensor sensing material according to claim 1, characterized in that the positively charged functional group includes a counter anion. Claim 5 An ion sensor sensing material according to claim 1, characterized in that the functional group providing the hydrogen bond comprises at least one of double hydrogen bond donors, namely urea, thiourea, squaramide, and croconamide. Claim 6 An ion sensor sensing material according to claim 1, characterized in that the functional group providing the hydrogen bond includes an electron-pulling group. Claim 7 An ion sensor sensing material according to claim 1, characterized in that the positively charged functional group and the hydrogen bonding functional group are connected by a direct bond or an alkyl chain composed of carbon. Claim 8 An ion sensor sensing material according to claim 1, characterized in that the metal included in the metal-macrocyclic composite molecule comprises at least one of Be, Mg, Ca, Sr, Ba, Ra, Fe, Cd, Cr, Co, Cu, Pb, Mn, Hg, Ni, Pt, Sn, and Zn. Claim 9 In claim 1, the molecular weight (M) of the metal-macrocyclic complex molecule w An ion sensor sensing material characterized by containing ) in the range of 100 to 100,000 g / mol. Claim 10 An ion sensor sensing material according to claim 1, characterized in that the metal-macrocyclic composite molecule is represented by the following chemical formula 1: [Chemical Formula 1] In the above chemical formula 1, R1 is a positively charged functional group, X is a negatively charged counter-anion, and C n (n = 0~10) is an alkyl chain composed of carbon, R2 is an organic molecule containing a double hydrogen bond donor or electron-pulling group, and M is a metal atom. Claim 11 An ion sensor sensing material according to claim 1, characterized in that the metal-macrocyclic composite molecule is represented by the following chemical formula 1a: [Chemical Formula 1a] In the above chemical formula 1a, M is a metal atom. Claim 12 An ion sensor comprising: a sensor substrate having an ion sensor sensing material of any one of claims 1 to 11 bonded by a covalent bond; and a sensor electrode patterned on the top of the sensor substrate to detect an electrical signal of the ion sensing material. Claim 13 An ion sensor according to claim 12, wherein the sensor substrate comprises at least one of glass, silicon, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonates (PC), polyethersulfone (PES), polyimide (PI), cyclic olefin copolymer (COC), and poly-dimethylsiloxane (PDMS). Claim 14 A method for fabricating an ion sensor comprising: (a) a step of preparing a uniform polymer-carbon nanotube dispersion solution by mixing a polymer containing a pyridyl group with carbon nanotubes; (b) a step of preparing a sensing layer based on a polymer-carbon nanotube composite material by uniformly applying and bonding the polymer-carbon nanotube dispersion solution onto a sensor substrate that has electrodes patterned and surface treated; (c) a step of preparing a metal-macrocyclic composite molecule; and (d) a step of fabricating an ion sensor by functionalizing the polymer-carbon nanotube composite material with the metal-macrocyclic composite molecule. Claim 15 A method for fabricating an ion sensor according to claim 14, wherein in step (a) above, the polymer and the carbon nanotube are dispersed and mixed in a solvent, and the solvent comprises at least one solvent selected from ethanol, methanol, propanol, butanol, isopropyl alcohol (IPA), dimethylformamide (DMF), acetone, acetonitrile, toluene, tetrahydrofuran, 1,2-dichlorobenzene, water, and mixtures thereof. Claim 16 A method for fabricating an ion sensor according to claim 14, characterized in that, in step (b) above, the polymer-carbon nanotube dispersion solution is applied to the sensor substrate using at least one coating process among a drop-coating process, a screen printing process, a spray coating process, a dip coating process, and an inkjet printing process. Claim 17 A method for fabricating an ion sensor according to claim 14, characterized in that, in step (b) above, the polymer forms a covalent bond through chemical bonding with a bromoalkyl chain functional group included in the sensor substrate that has been chemically modified through the surface treatment. Claim 18 A method for manufacturing an ion sensor according to claim 14, wherein, in step (b) above, the polymer-carbon nanotube composite material is bonded to the surface of the sensor substrate at a temperature included in the range of 25 ℃ to 300 ℃. Claim 19 A method for fabricating an ion sensor according to claim 14, wherein in step (c), the metal-macrocyclic complex molecule is formed by chelating a metal ion at the porphyrin center of a macrocyclic complex molecule in which the meso position of the porphyrin molecule is substituted with a positively charged functional group or a functional group that provides hydrogen bonding, and the synthesis temperature for chelating the metal ion is included in the range of 25 ℃ to 200 ℃. Claim 20 A method for fabricating an ion sensor according to claim 14, wherein, in step (d) above, a variety of metal-macrocyclic composite molecules are functionalized in the polymer-carbon nanotube composite material, and the electrical properties of the carbon nanotube are changed through one or more chemical interactions among electrostatic attraction, hydrogen bonding, and coordination bonding between the polymer-carbon nanotube composite material functionalized with the variety of metal-macrocyclic composite molecules and an ion component contained in the solution, and the ion sensor detects the ion component by measuring the change in electrical properties.
